1996
DOI: 10.1159/000177059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Renal Neutral Endopeptidase Inhibition on Sodium Excretion, Renal Hemodynamics and Neuro-hormonal Activation in Patients with Congestive Heart Failure

Abstract: We investigated the effects of inhibiting endogenous atrial natriuretic factor (ANF) metabolism on renal hemodynamics, sodium excretion and neurohormones in 12 patients with New York Heart Association functional class II congestive heart failure (CHF) due to left ventricular systolic dysfunction. In a randomized, placebo-controlled, double-blinded fashion, 8 patients received a single oral dose of candoxatril, an inhibitor of renal neutral endopeptidase, and 4 patients received placebo. Candoxatril treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
3
3
1
Order By: Relevance
“…15,16 Although isolated ACE inhibition may produce transient, minor natriuresis in mild HF, 33 this is unlikely in severe HF, when GFR is low and often falls further with ACE inhibition. 15,20,34 These results are consistent with a recent study in mild HF that demonstrated augmentation of natriuresis by omapatrilat compared with pure ACE inhibitor (fosinoprilat). 18 In our study, despite significant hemodynamic changes and falling renal perfusion pressure, ERPF increased with omapatrilat, most markedly in mild HF.…”
Section: Troughton Et Al Omapatrilat In Mild and Severe Heart Failuresupporting
confidence: 89%
See 1 more Smart Citation
“…15,16 Although isolated ACE inhibition may produce transient, minor natriuresis in mild HF, 33 this is unlikely in severe HF, when GFR is low and often falls further with ACE inhibition. 15,20,34 These results are consistent with a recent study in mild HF that demonstrated augmentation of natriuresis by omapatrilat compared with pure ACE inhibitor (fosinoprilat). 18 In our study, despite significant hemodynamic changes and falling renal perfusion pressure, ERPF increased with omapatrilat, most markedly in mild HF.…”
Section: Troughton Et Al Omapatrilat In Mild and Severe Heart Failuresupporting
confidence: 89%
“…While this pattern could be consistent with isolated ACE inhibition, the trend to improvement of GFR in severe HF is not an expected ACE inhibitor effect and presumably reflects neutral endopeptidase inhibition. 34 By contrast with these results, our previous studies in this severe HF model demonstrated a progressive decline in endogenous creatinine clearance with repeated doses of the ACE inhibitor captopril. 19 The beneficial renal hemodynamic effects of omapatrilat in this study may be mediated by local enhancement of ANP, BNP, or urodilatin levels within the kidney.…”
Section: Troughton Et Al Omapatrilat In Mild and Severe Heart Failurecontrasting
confidence: 64%
“…16,17 In agreement with earlier studies, 1,13 ADM increased urinary cAMP and sodium excretion and more than maintained urinary output in the face of larger blood pressure reductions. In addition to any effects of NEP inhibition and ADM administration on tubular reabsorption and renal vascular resistance and increases in renal blood flow, 24 increased glomerular filtration (as assessed by increased creatinine clearance) appears to have contributed to the natriuretic effects observed with both treatments in the present study.…”
Section: Renal Functionsupporting
confidence: 89%
“…The hypotensive effect of ADM appears to be primarily due to a direct affect on arterial tone, 22 whereas the rise in CO presumably reflects a positive inotropic action 23 and the fall in cardiac afterload. Similar hemodynamic responses to separate ADM 1,13-15 and NEP inhibition 16,17 have previously been reported in HF. Combined treatment induced greater reductions in cardiac preload and afterload and increments in CO than during ADM infusion alone.…”
Section: Hemodynamicssupporting
confidence: 84%
See 1 more Smart Citation